RANCANGAN SISTEM INFORMASI RUMAH SAKIT SUBSISTEM: PENGELOLAAN INVENTORY DAN TRANSAKSI OBAT - Noerlina, Noerlina (CommIT (Communication and Information Technology) Journal, 2009)
Hospitals have always manage their supplies used during their operational activities. However, hospitals still have difficulties in raising performance of supply management to optimum standards. This occurs because hospitals still implement a manual supply recording system therefore causing supply information needed to analyse supply management to be inaccurate, time consuming, and thus bigger costs.The purpose of this study is to conduct analysis of the the current hospital inventory system and design an inventory information system. Methods used are bibliography study, analysis method and design method. Analysis method is used to formulate the hospital’s problems. Design method is used to design a new system to solve the said problems in the hospital. The aims to be achieved are reports corresponding with inventory management and medicine transaction and interface that can be used to manage the inventory and medicine transaction. Conclusion is that the new system is expected to facilitate the related party in managing inventory and medicine transaction, and also producing accurate reports.Keywords: design, inventory, pharmacy, hospital information systems